Transform circuit analysis for engineering and technology - Stanley, William D. (Prentice Hall, 1997)
This revision continues to present the fundamentals of transient circuit and system analysis with an emphasis on the Laplace transform and pole-zero approach for analyzing and interpreting problems. An application-oriented treatment of transform circuit analysis is carefully aimed at engineering technology or applied engineering programmes, and a full development of transient phenomena in both time domain and frequency domain is presented. There is also an introduction to discrete-time systems and digital signal processing.